2013
DOI: 10.5312/wjo.v4.i4.186
|View full text |Cite
|
Sign up to set email alerts
|

Historically significant events in the discovery of RANK/RANKL/OPG

Abstract: After it was suggested 30 years ago that the osteoblast lineage controlled the formation of osteoclasts, methods were developed that established this to be the case, but the molecular controls were elusive. Over more than a decade much evidence was obtained for signaling mechanisms that regulated the production of a membrane -bound regulator of osteoclastogenesis, in the course of which intercellular communication in bone was revealed in its complexity. The discovery of regulation by tumor necrosis factor liga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 92 publications
1
37
0
2
Order By: Relevance
“…The effects of vitamin D on osteoclastic activity has largely been established to be mediated via 1,25(OH) 2 D 3 activity on osteoblasts, which regulates the secretion of the key osteoclastogenesis factor, RANKL. RANKL/OPG ratio is an index of osteoclastogenic stimulation (Tanaka et al 2011) and plays a key role in the regulation of bone metabolism (Martin 2013). In this study, we found that high-dose 1,25(OH) 2 D 3 obviously increased the expression of RANKL and decreased the expression of OPG.…”
Section: Discussionmentioning
confidence: 96%
“…The effects of vitamin D on osteoclastic activity has largely been established to be mediated via 1,25(OH) 2 D 3 activity on osteoblasts, which regulates the secretion of the key osteoclastogenesis factor, RANKL. RANKL/OPG ratio is an index of osteoclastogenic stimulation (Tanaka et al 2011) and plays a key role in the regulation of bone metabolism (Martin 2013). In this study, we found that high-dose 1,25(OH) 2 D 3 obviously increased the expression of RANKL and decreased the expression of OPG.…”
Section: Discussionmentioning
confidence: 96%
“…7 The breakthrough in understanding osteoclastogenesis came from the discovery that receptor activator of NF-κB ligand (RANKL) and macrophage colony-stimulating factor (M-CSF) have essential roles in stimulating monocyte-macrophage lineage cells to differentiate into mature and functional OCs. [8][9][10] Currently, known crucial RANKL downstream transcription factors and genes include active nuclear factor of activated T cells (NFAT) 2, c-Fos, β 3 -integrin, Cathepsin K, and matrix metallopeptidase 9. 11,12 Among these, NFAT2 acts as a master switch for the terminal differentiation of OCs.…”
mentioning
confidence: 99%
“…As members of the tumor necrosis factor superfamily, the molecular triad of osteoprotegerin (OPG)/receptor activator of nuclear factor κβ (RANK)/receptor activator of nuclear factor κβ ligand (RANKL) represents a key cytokine system for regulating bone metabolism (7,8). In OA, remodeling of the subchondral bone is reported to be RANKL-dependent, and osteoblasts express RANKL in subchondral bone (4,9).…”
Section: Introductionmentioning
confidence: 99%